AGE, SEX, AND TYPES OF OCCUPATION WITH HISTOPATHOLOGICAL TYPES IN PATIENTS WITH OCULAR SURFACE SQUAMOUS NEOPLASIA (OSSN) IN A TERTIARY HOSPITAL IN SURABAYA, INDONESIA - Stella Agatha Widjaja; Delfitri Lutfi; Linda Dewanti; Alphania Rahniayu; Fitria Kusumastuti (Majalah Biomorfologi, 2024)
Highlights The histopathological types of OSSN were significantly associated with age and occupation. The study's findings enhance the understanding of OSSN in Indonesia and emphasize the importance of UV exposure, occupation, and age in its development.   Abstract Background:  Ocular Surface Squamous Neoplasia (OSSN) is a spectrum of tumors affecting the conjunctiva and cornea, in which a more invasive type of OSSN has a higher recurrence rate. As a tropical country, Indonesia is constantly exposed to intense ultraviolet (UV) radiation, the main risk factor for OSSN. Despite this, there are very few studies regarding OSSN in Indonesia. Objective:  This study aimed to analyze the association between sociodemographic characteristics such as age, sex, and types of occupation (outdoor and indoor) and histopathological types of OSSN to fill the gap in research and contribute to early diagnostic strategies. Material and Method: Sociodemographic and histopathological data were extracted from the medical records of patients who were histopathologically diagnosed with OSSN at Dr. Soetomo General Hospital from 2017 to 2021. Data from 88 samples that met the inclusion and exclusion criteria were classified and analyzed with descriptive statistics and a two-sided Fisher's exact test using SPSS version 27.0 (IBM Corp., Armonk, N.Y., USA). Result: The exact test results of the two-sided fisher revealed a statistically significant relationship between age (p = 0.0004) and occupation type (p = 0.049) with histopathological types of OSSN. However, no significant association was found between sex and histopathological types of OSSN (p = 0.130). Conclusion: Age and occupation were found to have a significant association with the histopathological types of OSSN, reinforcing the need for further exploration of its strength and nature to be considered by future researchers.